Rock mechanics testing machine. - Dengke Yang (842532) (2025)
Open rock masses are subject to prolonged loading and freeze-thaw cycles in cold regions. In this study, we take saturated fissured red sandstone as object to investigate the long-term mechanical response characteristics of fractured rock under freeze-thaw conditions. Experimental tests were conducted to analyze the creep characteristics of the rock after freeze-thaw cycles, considering different freeze-thaw frequencies and fracture orientations. The results reveal that (1) freeze-thaw cycles exert a significant influence on the rock’s creep behavior, with axial strain, instantaneous strain, and creep strain increasing progressively with the number of freeze-thaw cycles; (2) dual-fractured rock samples with varying fracture angles exhibit distinct differences in creep phenomena, where increased fracture angles result in pronounced increases in instantaneous and creep strains, and higher horizontal stress levels lead to greater strain generation; (3) all rock samples with different pre-existing fractures exhibit rock bridge breakthrough during creep failure, and the variation in fracture angle affects the failure mode; (4) and the long-term strength of the rock varies with changes in fracture angle and freeze-thaw cycle frequency, showing an increasing trend with greater fracture angles but a rapid decrease with increasing freeze-thaw cycles. These findings provide valuable insights for engineering design and risk assessment of open rock masses in cold regions. This study has guiding significance for the safety construction of rock mass engineering in cold regions.